2015
DOI: 10.1038/srep12547
|View full text |Cite
|
Sign up to set email alerts
|

Large-mode-area single-mode-output Neodymium-doped silicate glass all-solid photonic crystal fiber

Abstract: We have demonstrated a 45 μm core diameter Neodymium-doped all-solid silicate glass photonic crystal fiber laser with a single mode laser output. The structure parameters and modes information of the fiber are both demonstrated by theoretical calculations using Finite Difference Time Domain (FDTD) method and experimental measurements. Maximum 0.8 W output power limited by launched pump power has been generated in 1064 nm with laser beam quality factor M2 1.18.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…The spatially complex structure of English landscapes and the creation of flower rich habitats under the agri-environment schemes may mean that a sufficient continuity of foraging resources do exist that allow wild bees to benefit from the short flowering period of oilseed rape. Ultimately, the intensive nature of oilseed rape crop management, in particular its dependence on insecticides, means that its value as a foraging resource for wild bees may be outweighed by the management required to ensure crop yields 32 . However, it may be possible to cultivate oil-seed rape without extensive use of neonicotinoids: a recent UK based analysis demonstrated that on average neonicotinoid seed treatments do not boost farmer profits 32 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The spatially complex structure of English landscapes and the creation of flower rich habitats under the agri-environment schemes may mean that a sufficient continuity of foraging resources do exist that allow wild bees to benefit from the short flowering period of oilseed rape. Ultimately, the intensive nature of oilseed rape crop management, in particular its dependence on insecticides, means that its value as a foraging resource for wild bees may be outweighed by the management required to ensure crop yields 32 . However, it may be possible to cultivate oil-seed rape without extensive use of neonicotinoids: a recent UK based analysis demonstrated that on average neonicotinoid seed treatments do not boost farmer profits 32 .…”
Section: Resultsmentioning
confidence: 99%
“…Ultimately, the intensive nature of oilseed rape crop management, in particular its dependence on insecticides, means that its value as a foraging resource for wild bees may be outweighed by the management required to ensure crop yields 32 . However, it may be possible to cultivate oil-seed rape without extensive use of neonicotinoids: a recent UK based analysis demonstrated that on average neonicotinoid seed treatments do not boost farmer profits 32 .…”
Section: Resultsmentioning
confidence: 99%
“…Compared to solid-core fibers, HCFs with guiding of light in an air core (ideally in a vacuum) have been extremely more appealing since their first realization in 1999 [52] because of their lower Rayleigh scattering, lower nonlinearity, lower transmission loss, and higher laser damage threshold in air holes. [135][136][137][138][139][140][141][142][143][144][145][146][147] In 2018, an antiresonant HCF transmitted a high-power laser of up to ≈45 W average power. [148] In 2020, a nested antiresonant nodeless fiber was demonstrated to achieve the current record loss of ≈0.28 dB km −1 at 1550 nm, while its theoretical loss limit is less than 0.1 dB km −1 , lower than that of the standard singlemode fiber.…”
Section: The Progress In Optical Fibersmentioning
confidence: 99%
“…Burada, lazer kaynağından gelen ışık, bir polarizör denetleyicisi aracılığıyla önerilen algılayıcıya doğrusal olarak polarize bir şekilde, Ref. [30]'un makalesinde gösterildiği gibi temel modda yayınım yapması sağlanabilmektedir. Algılayıcıda oluşan rezonans durumu, optik spektrum analizörü (OSA) tarafından tespit edilir ve veriler, bilgisayar tarafından analiz edilir.…”
Section: Sayısal Modellemeunclassified